The Implementation Usage of Youtube Media on Listening Ability of English Students During the Covid-19 Pandemic - Manihuruk, Leonita Maria Efipanias; Nababan , Irene Adryani (International Journal of Multidisciplinary: Applied Business and Education Research, 2022)
This research is motivated by learning English listening for students during the covid-19 pandemic which has not been carried out properly because students' understanding of listening skills is still lacking. The teaching and learning process during the pandemic is increasingly difficult for students to experience, resulting in disruption of the teaching and learning process. This also reduces the activeness of students in participating in listening learning. The learning media used are also still less effective, moreover the learning techniques used are still less varied. The purpose of this study was to determine the implementation of the use of Youtube media on the English listening skills of HKBP Nommensen Pematangsiantar University students during the covid-19 pandemic. The research method used is a quasi-experiment without a control class. The steps that will be carried out in this research are; 1) Conducting Pre Test; 2) Doing treatment using Youtube media; 3) Do a Post Test, then conclude. Learning outcomes can be seen how the differences in the increase in learning outcomes in the pretest and posttest can be seen. In the experimental class there was an increase in classical learning outcomes of 72,3287%. Conclusion from the research Overall, the implementation of the use of YouTube can be designed to be an effective learning medium for Transactional Listening tasks.